Aspectos do sistema de produção agrícola, industrial e de qualidade do vinho: revisão de literatura - Guardiano, Arthur Vicari (Universidade Federal de São Carlos, 2021)
The work aimed to carry out a literature review regarding the agricultural and industrial system of the wine production chain, the classification and diversity of types of wines and their factors related to the quality of the drink, such as physical-chemical and sensory aspects. Therefore, a bibliographical review was carried out, identifying the works relevant to the proposed objective. Thus, the physiology of the vine, its agronomic particularities, the wine production system, its characteristics and classifications, as well as the wine market in Brazil and in the world were analyzed.
Aspects of the agricultural, industrial and wine quality production system: literature review
Keywords: Vinificação; Produção de uvas; Análise sensorial; Classificação de vinhos; CIENCIAS AGRARIAS